2010
DOI: 10.1371/journal.pone.0012617
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in a Cohort of HIV Infected Pregnant and Non-Pregnant Women Treated with Nevirapine versus Non-Nevirapine Antiretroviral Medication

Abstract: BackgroundPredictors of adverse events (AE) associated with nevirapine use are needed to better understand reports of severe rash or liver enzyme elevation (LEE) in HIV+ women.MethodologyAE rates following ART initiation were retrospectively assessed in a multi-site cohort of 612 women. Predictors of onset of rash or LEE were determined using univariate and multivariate analyses.Principal FindingsOf 612 subjects, 152 (24.8%) initiated NVP-based regimens with 86 (56.6%) pregnant; 460 (75.2%) initiated non-NVP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 27 publications
0
26
2
1
Order By: Relevance
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
“…Participants with hepatitis B or C infection were excluded from 2 studies, 4,27 whereas 7 studies reported the prevalence of hepatitis co-infection. [28][29][30]34,[36][37][38] NVP was initially commenced at 200 mg daily for 14 days in all women. The CD4 cut-off was 250 cells/µl for toxicity analyses in all studies, except for one (CD4 cut-off of 200 cells/ µl).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations